2011
DOI: 10.1016/j.applthermaleng.2011.03.041
|View full text |Cite
|
Sign up to set email alerts
|

Analysis and comparison of municipal solid waste and reject fraction as fuels for incineration plants

Abstract: ABSTRACTcalorific value (similar to that for some types of wood) corresponds to RDF, so its incineration will be more profitable than using MSW as fuel.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
55
1
3

Year Published

2013
2013
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 108 publications
(66 citation statements)
references
References 21 publications
7
55
1
3
Order By: Relevance
“…The factor that greatly affects NCV is moisture, and this is shown in summer months where the greatest reduction in NCV value is observed. As presented by Montejo et al (2011), the found NCV can be comparable with the MSW analyses, on as received basis. Net calorific value is considered an economical indicator, and the classification according to CEN 343 is class 4.…”
Section: Analysessupporting
confidence: 66%
See 1 more Smart Citation
“…The factor that greatly affects NCV is moisture, and this is shown in summer months where the greatest reduction in NCV value is observed. As presented by Montejo et al (2011), the found NCV can be comparable with the MSW analyses, on as received basis. Net calorific value is considered an economical indicator, and the classification according to CEN 343 is class 4.…”
Section: Analysessupporting
confidence: 66%
“…This indicates that the produced RDF has significantly higher moisture content than other RDF samples studied. (Liu et al 2001;Wan et al 2008;Montejo et al 2011) More specifically, from the pre-drying procedure followed for all of the increments of each sample, moisture was found to be more than 32 % in the majority of the samples. The maximum moisture found in a daily increment was 47.57 %, and the minimum was 31.60 %.…”
Section: Analysesmentioning
confidence: 99%
“…In the past, the MSW has mainly been deposited on the landfills.Because of its simplicity, such disposal has a low price, but it is contrary to the order of hierarchy of waste disposal [9,10] and the previously mentioned EU waste management directives and documents. MSW contains mostly organic, biodegradable fraction which occupies 55 % of the total amount of waste [8].…”
Section: Mechanical and Biological Waste Treatmentmentioning
confidence: 89%
“…[8,35], 10 600 kJ/kg in UK [9,36] and 9999 kJ/kg in India [8]. For the RDF, such values are 10 110 kJ/kg in Italy and 13 733 kJ/kg for Taiwan [8].The different lower heating values of MSW as well as of RDF are result of their different compositions, especially emphasized heating values of MSW.…”
Section: Comparison Of Municipal Solid Waste and Rdf Fractionmentioning
confidence: 99%
See 1 more Smart Citation